Epistemological Perspective of Mathematics as the basis of science - Lucas Cabello, Adalberto (2019)
The present research study sought to establish the epistemological perspective of mathematics as the basis of science. Focused on the fundamental or basic research, the reason, our purpose was to deepen, increase and as much as possible generate knowledge about epistemology of mathematics, and mathematics as the basis of science. Near the study's epilogue, we arrived at the following result: mathematics is the basis of the sciences, because it is the nature's and cosmos' language and both are expressed only through mathematics; similarly, because the measurement is a basic factor for the construction of scientific knowledge, discover new theories and laws. To end up, we came to the conclusion that it was established that mathematics is the basis of sciences, essentially of the natural sciences and to a lesser extent of the social sciences. Philosophy has a reflexive relationship with mathematics and mathematics from an epistemological perspective are the object of scientific research.